Enhancing Digital Political Literacy through a Community-Based Platform to Improve Public Participation in Urban Neighborhoods: A Community Service Program in Malang City, Indonesia - Asep Nurjaman; Gonda Yumitro; Tobroni Tobroni (Lembaga Dongan Dosen, 2026)
Local democracy in Indonesia still struggles at the neighborhood level. Most people just aren’t that politically savvy, and not many jumps in to participate. That’s a big deal, especially since this is where decisions hit closest to home. For this reason, we rolled up our sleeves and launched a community service program in Malang City called WargaMelek.id. The goal was pretty clear: boost digital political literacy and get people more involved, for real, not just on paper. We worked directly with residents, neighborhood leaders, and youth groups in Dinoyo and Tlogomas. The program ran for two years, from 2025 to 2026. We kept things hands-on and local. There were workshops, training sessions on digital political literacy, and a number of activities where people helped shape the digital platform itself. We didn’t just drop in and leave—we stuck around for mentoring and support all the way through. Participants’ digital political literacy scores jumped by 41 percent. Attendance at local planning forums climbed from 48 per cent to 67 per cent, and we saw way more women and young people getting involved. In addition, over 300 people started using the platform actively. The community even set up a Village Digital Community Management Team to keep things running after the program wrapped up. The design of digital programs that meet people where they are and keep them involved – you really can build stronger civic awareness, open up new spaces for participation, and make local government more inclusive and transparent.